Pyrroloquinoline Quinone Regulates Enteric Neurochemical Plasticity of Weaned Rats Challenged With Lipopolysaccharide - Shi, Chenyu; Xu, Song; Huang, Caiyun; Wang, Zijie; Wang, Wenhui; Ming, Dongxu; Yin, Xindi; Liu, Hu; Wang, Fenglai (Frontiers in Neuroscience, 2022)
Enteric nervous system is important for intestinal barrier to defend and regulate inflammation in the intestine. This study aims to research the effect of pyrroloquinoline quinone (PQQ) on regulating neuropeptides secretion by ENS neurons of rats challenged with lipopolysaccharide (LPS) to create enteritis. Thirty Sprague Dawley rats were divided into five groups including: basal (CTRL), basal plus LPS challenge (LPS), basal with 2.5 mg/kg b.w./day of PQQ plus challenge with LPS (PQQ 2.5), basal with 5.0 mg/kg b.w./day PQQ plus challenge with LPS (PQQ 5) and basal with 10.0 mg/kg b.w./day PQQ plus challenge with LPS (PQQ 10). After treatment with basal diet or PQQ for 14 days, rats were challenged with LPS except for the CTRL group. Rats were euthanized 6 h after LPS challenge. Rats showed increased average daily gain in PQQ treatment groups (P < 0.05). Compared with LPS group, PQQ 5 and PQQ 10 rats showed increased villus height and villus height/ crypt depth of jejunum (P < 0.05). In PQQ treatment groups, concentrations of IL-1β and TNF-α in serum and intestine of rats were decreased, and IL-10 concentration was increased in serum compared with the LPS group (P < 0.05). Compared with LPS group, the concentration of neuropeptide Y (NPY), nerve growth factor (NGF), vasoactive intestinal peptide (VIP), substance P (SP), calcitonin gene-related peptide (CGRP) and brain-derived neurotrophic factor (BDNF) in serum were decreased in PQQ treatment groups (P < 0.05). Compared with LPS group, ileal mRNA levels for BDNF, NPY and NGF were decreased in PQQ treatment groups (P < 0.05). Jejunal concentrations of SP, CGRP, VIP, BDNF, NPY and NGF were decreased in PQQ treatment groups compared with LPS group (P < 0.05). Compared with LPS group, phosphor-protein kinase B (p-Akt)/ Akt levels in jejunum and colon were decreased in PQQ treatment groups (P < 0.05). In conclusion, daily treatment with PQQ improved daily gain, jejunal morphology, immune responses. PQQ regulated enteric neurochemical plasticity of ENS via Akt signaling pathway of weaned rats suffering from enteritis.